Body composition, dietary intake, and iron status of female collegiate swimmers and divers - Petersen, H. L.; Peterson, C. T.; Reddy, M. B.; Hanson, K. B.; Swain, J. H.; Sharp, R. L.; Alekel, D. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study determined the effect of training on body composition, dietary intake, and iron status of eumenorrheic female collegiate swimmers (n = 18) and divers (n = 6) preseason and after 16 wk of training. Athletes trained on dryland (resistance, strength, flexibility) 3 d/wk, 1.5 h/d and in-water 6 d/wk, nine, 2-h sessions per week (6400 to 10,000 kJ/d). Body-mass index (kg/m2; P = 0.05), waist and hip circumferences (P = 0.0001), whole body fat mass (P = 0.0002), and percentage body fat (P = 0.0001) decreased, whereas lean mass increased (P = 0.028). Using dual-energy X-ray absorptiometry, we found no change in regional lean mass, but fat decreased at the waist (P = 0.0002), hip (P = 0.0002), and thigh (P = 0.002). Energy intake (10,061 ± 3617 kJ/d) did not change, but dietary quality improved with training, as reflected by increased intakes of fiber (P = 0.036), iron (P = 0.015), vitamin C (P = 0.029), vitamin B-6 (P = 0.032), and fruit (P = 0.003). Iron status improved as reflected by slight increases in hemoglobin (P = 0.046) and hematocrit (P = 0.014) and decreases in serum transferrin receptor (P = 0.0001). Studies are needed to further evaluate body composition and iron status in relation to dietary intake in female swimmers.